The shape shifter [compact disc, unabridged] - Hillerman, Tony (Hillerman, Tony. Leaphorn & Chee novel., 2006)
Retired from the Navajo Tribal Police, Lieutenant Joe Leaphorn is called upon once again to solve a crime. This time it's Joe's last case, a case that remains unsolved and contines to haunt him.